Coulomb drag propulsion experiments of ESTCube-2 and FORESAIL-1 - Iakubivskyi Iaroslav; Janhunen Pekka; Praks Jaan; Allik Viljo; Bussov Kadri; Clayhills Bruce; Dalbins Janis; Eenmäe Tõnis; Ehrpais Hendrik; Envall Jouni; Haslam Sean; Ilbis Erik; et al. (Elsevier Ltd, 2022)
This paper presents two technology experiments – the plasma brake for deorbiting and the electric solar wind sail for interplanetary propulsion – on board the ESTCube-2 and FORESAIL-1 satellites. Since both technologies employ the Coulomb interaction between a charged tether and a plasma flow, they are commonly referred to as Coulomb drag propulsion. The plasma brake operates in the ionosphere, where a negatively charged tether deorbits a satellite. The electric sail operates in the solar wind, where a positively charged tether propels a spacecraft, while an electron emitter removes trapped electrons. Both satellites will be launched in low Earth orbit carrying nearly identical Coulomb drag propulsion experiments, with the main difference being that ESTCube-2 has an electron emitter and it can operate in the positive mode. While solar-wind sailing is not possible in low Earth orbit, ESTCube-2 will space-qualify the components necessary for future electric sail experiments in its authentic environment. The plasma brake can be used on a range of satellite mass classes and orbits. On nanosatellites, the plasma brake is an enabler of deorbiting – a 300-m-long tether fits within half a cubesat unit, and, when charged with - 1 kV, can deorbit a 4.5-kg satellite from between a 700- and 500-km altitude in approximately 9–13 months. This paper provides the design and detailed analysis of low-Earth-orbit experiments, as well as the overall mission design of ESTCube-2 and FORESAIL-1.